Marketing Strategy Analysis Using the Quantitative Strategic Planning Matrix (QSPM) to Increase Sales Furniture - Azaluddin Azaluddin; Jamdia Jamdia (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2022)
Sarah's furniture trade company is a company that manufactures industrial furniture such as cabinets, chairs, and tables. Sarah's Furniture Trading Business's concern is that the company's revenues from 2019 to 2020 declined owing to internal and external factors. The goal of this research is to discover the marketing strategy employed by the Sarah Furniture Trading Business, as well as how the marketing strategy employs the Quantitative Strategic Planning Matrix approach to enhance sales at the Sarah Furniture Trading Business. Sarah's furniture trade business received a total score of 22.75 based on the IFE matrix analysis, while the EFE matrix analysis received a score of 18.48. Sarah's furniture trading business IE matrix findings are in the V quadrant, with an IFE matrix of 22.75 and an EFE of 18, 48, indicating that the company may overcome it through product quality, product market development, and market penetration methods. The SWOT matrix study produced nine strategies from which Sarah's furniture trade business may choose. The highest prioritized alternative strategy, according to the QSPM matrix, is to maintain product quality with a TAS score of 12.